248 Epigenetic changes in firefighters. (24th April 2018) - Jeong, Kyoung Sook; Zhou, Jin; Jacobs, Elizabeth; Griffin, Stephanie C; Littau, Sally; Gulotta, John; Moore, Paul; Dearmon-Moore, Devi; Peate, Wayne F; Burgess, Jeffery L
Abstract : Introduction: Firefighters are exposed to carcinogens and have elevated cancer rates. Cancer may be caused by activation of oncogenes or inhibition of tumour suppressor genes, such as through alterations in microRNA (miRNA) concentrations and DNA methylation. We hypothesised that occupational exposures in firefighters would lead to epigenetic changes associated with activation of cancer pathways and increased cancer risk. We designed this study to compare epigenetic changes in incumbent firefighters and new recruits. Methods: At the time of subject selection, the study population consisted of 119 incumbents and 70 recruits. From this group, 108 subjects were randomly selected for miRNA analysis and 96 for DNA methylation analysis, both evenly divided among incumbents and recruits. Only non-smoker male firefighters were included in the final comparison. MiRNAs and DNA methylation were measured with the nCounter Human v3 miRNA expression assay with over 828 miRNAs and the Illumina MethylationEPIC 850 k chips, respectively. Result: After adjusting for age and BMI, miR-1260a, miR-145–5 p, miR-181c-5p, miR-331–3 p, miR-361–5 p, and miR584–3 p were significantly downregulated in incumbent firefighters. MiR-208b-5p, miR-30e-3p, and miR-486–3 p were significantly overexpressed in incumbents. Controlling the genome-wide false discovery rate at 5%, 22 CpGs were annotated to promoter regions of a gene and were hypermethylated in the incumbents including YIPF6, HELB, SYT5 and DVL2. Discussion: MiR-181c-5p, miR-145–5 p, and miR-584–3 p are involved in tumour suppression. MiR-30e-3p is upregulated in skin cancer and is a poor prognostic factor in lung cancer. Co-amplification of the YIPF6 gene with the androgen receptor may stimulate prostate tumour progression. Aberrant activation of HELB reduces genomic stability, a hallmark of cancer. SYT may have a novel function in breast cancer. DVL2 is a part of the Wnt signalling pathway involved in multiple cancers. These epigenetic biomarkers of carcinogenic exposure in firefighters should be further evaluated in larger studies.